2013
DOI: 10.1016/j.jcmg.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Term Prognostic Value of Reversible Perfusion Deficit Diagnosed by Adenosine CMR

Abstract: Adenosine perfusion CMR provides excellent risk stratification and intermediate-term prognostic value in patients with stable coronary artery disease. The presence of a myocardial perfusion deficit is an incremental prognostic risk factor over other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…30 Buckert et al have confirmed that the presence of late gadolinium enhancement is a strong clinical predictor of cardiovascular events in patients with stable coronary artery disease. 10,31,32 Rizzi et al have demonstrated in the MESA study that several techniques can be used to quantify infarction dimension, such as: visual technique, planimetry, the standard deviation technique, full width at half maximum, and the correction of image noise. 33 Semiautomatic analysis with manual correction and removal of artifacts is the first choice among diagnostic methods to quantify the infarction zone and fibrosis.…”
Section: Assessment Of Myocardial Viabilitymentioning
confidence: 99%
“…30 Buckert et al have confirmed that the presence of late gadolinium enhancement is a strong clinical predictor of cardiovascular events in patients with stable coronary artery disease. 10,31,32 Rizzi et al have demonstrated in the MESA study that several techniques can be used to quantify infarction dimension, such as: visual technique, planimetry, the standard deviation technique, full width at half maximum, and the correction of image noise. 33 Semiautomatic analysis with manual correction and removal of artifacts is the first choice among diagnostic methods to quantify the infarction zone and fibrosis.…”
Section: Assessment Of Myocardial Viabilitymentioning
confidence: 99%
“…cardiac episodes after 3 years was significantly greater in patients with normal CMR---dobutamine or CMR---adenosine. 64 In addition, a normal stress test predicted better the episodes that the cardiovascular risk factors or the segmental contractility defects. Other studies have proved the usefulness and prognostic value of CMR---dobutamine when it is not possible to perform stress echocardiography examinations.…”
Section: Inducible Myocardial Ischemiamentioning
confidence: 99%
“…It is viable to reliably detect and visualize myocardial ischemia as well as necrotic tissue in one single exam [11]. It has been shown to provide important prognostic information in patients with known or suspected CAD [12][13][14][15][16][17][18][19]. There remains however, a gap in the current evidence base and that gap is a lack of standardization for the quantification of ischemia [20].…”
Section: Introductionmentioning
confidence: 99%